THE IMPLEMENTATION OF SOCIAL LEARNING STRATEGY FOR LEARNING ENGLISH FOREIGN LANGUAGE IN VOCATIONAL HIGH SCHOOL - Wildan Munirul Faqih; Dias Andris Susanto; Minumi Wening Budi Nurani (Lumbung Pare Cendekia, 2023)
This study aims to investigate students' perceptions of Sosial Learning Strategies in improving various English as a Foreign Language (EFL) language skills in SMK N 4 Semarang. A descriptive qualitative method was used with a questionnaire survey to collect data from 66 students of SMK N 4 Semarang who completed the 4 items of the Strategy Inventory for Language Learning (SILL) questionnaire and a Background Characteristics survey. The study's findings indicate that how English is used in practice affects how well it is learned. The findings showed a connection between using social strategies and effectively learning English. The most commonly used social strategies are “I review English lessons with my closest friends”.